2013
DOI: 10.1016/j.fertnstert.2012.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Defective protein kinase A and C pathways are common causes of disordered zona pellucida (ZP)–induced acrosome reaction in normozoospermic infertile men with normal sperm-ZP binding

Abstract: Defective upstream of PKC and PKA pathways are highly associated with disordered ZPIAR in normozoospermic infertile men with normal sperm-ZP binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In agreement with our results, the studies conducted in humans by Liu et al. () show that in normospermic individuals, the prevalent cause of infertility is a failure in signal transduction when PKA is defective, reinforcing the key role played by cAMP‐dependent kinase.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, the studies conducted in humans by Liu et al. () show that in normospermic individuals, the prevalent cause of infertility is a failure in signal transduction when PKA is defective, reinforcing the key role played by cAMP‐dependent kinase.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of PKC can induce acrosome exocytosis in sperm (Breitbart et al, ; Rotem et al, ; Toole et al, ), and key PKC substrates, such as MARCKS protein, play an important role in the process (Rodriguez Peña et al, ). Studies indicate that disruption of PKA and PKC pathways are a major cause of disordered zona pellucida‐induced acrosome reaction in normozoospermic infertile men with normal sperm‐zona pellucida binding (Liu et al, ). Our current data support a physiological role for sperm PKCδ in the regulation of zona pellucida interaction.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was found that MARCKS protein is phosphorylated by PKC during human acrosomal exocytosis (Rodriguez Pena et al, 2013) supporting the role of PKC in acrosomal exocytosis preparation. Also, PKC activity has been involved in early events leading to acrosomal exocytosis in other mammals, and a more recent work demonstrated that PMA enhances ZP-induced Acrosomal reaction (AR) in human sperm (Liu et al, 2013). Despite our previous results (Teijeiro & Marini, 2012), which showed no effect of PMA on boar sperm acrosome reaction, here we demonstrate a slight but significant effect of PMA on acrosome reaction, detected by a more sensitive and Figure 5 Effect of PMA-induced PKC activation and PKA inhibition over changes in plasma membrane lipids organization.…”
Section: Discussionmentioning
confidence: 99%